Lithium titanium aluminum phosphate solid electrolyte as well as preparation method and application thereof

Through the coordinated cooperation of boron, niobium and/or zinc, the low conductivity and brittleness of titanium aluminum lithium solid electrolyte are solved, achieving efficient electrochemical performance improvement and energy consumption reduction.

CN119725694APending Publication Date: 2025-03-28TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311252140.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing solid electrolytes of titanium aluminum lithium phosphate have problems such as low grain boundary conductivity, high brittleness of the electrolyte and large interface resistance, and it is difficult to achieve uniform distribution of elements and no segregation of the doping method.

Method used

Through the coordinated cooperation of boron and niobium and/or zinc, the ionic conductivity of the solid electrolyte of titanium aluminum phosphate is improved, and the production energy consumption and the heterogeneous phase generation of materials are reduced by adjusting the sintering temperature and process parameters.

Benefits of technology

It significantly improves the ionic conductivity of solid electrolytes, improves electrochemical performance, reduces sintering temperature and production energy consumption, and achieves uniform distribution of doped elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725694A_ABST
    Figure CN119725694A_ABST
Patent Text Reader

Abstract

The invention provides a lithium titanium aluminum phosphate solid electrolyte and a preparation method and application thereof. The lithium titanium aluminum phosphate solid electrolyte is doped with a first doping element and a second doping element; wherein the first doping element comprises boron, and the second doping element comprises niobium and / or zinc. According to the invention, through synergistic cooperation of boron and other doping elements (niobium and / or zinc), the ionic conductivity of the lithium aluminum titanium phosphate solid electrolyte is obviously improved, the sintering temperature in the preparation process is reduced, and the production energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid-state batteries and relates to a lithium aluminum titanium phosphate solid electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion solid-state batteries have attracted attention and research in the battery industry for their high capacity and good safety performance. One of the key materials for solid-state batteries is solid electrolytes. The solid electrolytes currently under development in the industry can be roughly divided into three categories: sulfides, inorganic oxides, and polymers. Among them, sulfides have the highest ion conductivity, but are more difficult to produce and apply, while polymers have lower ion conductivity. Both of the above electrolytes are difficult to apply in the market in the short term. Inorganic oxide solid electrolytes have the advantages of high ion conductivity, good mechanical strength, and simple preparation, and are the most likely solid electrolytes to be applied in the short term.

[0003] LATP(Li 1+x Al x Ti 2-x (PO 4 ) 3 ) is a material that has been studied more in oxide solid electrolytes and belongs to LiTi 2 (PO 4 ) 3 Derived NASICON structure (LiTi 2 (PO 4 ) 3 By sharing O atoms, TiO 6 Octahedron and PO 4 Tetrahedrons are connected to form a three-dimensional framework. In LTP, due to the Ti 4+ Partly Al 3+ The obtained LATP has a well-structured skeleton, which is beneficial to Li + Rapid migration.

[0004] The preparation method includes solid phase sintering method, sol-gel method or electrochemical preparation method. For example, CN111180703A dissolves tetrabutyl titanate, aluminum nitrate nonahydrate, ammonium dihydrogen phosphate and lithium acetate dihydrate in anhydrous ethanol, stirs the solution until the anhydrous ethanol is completely volatilized to obtain dry powder, and then heats the obtained dry powder to obtain LATP powder. CN111233458A discloses a lithium aluminum titanium phosphate solid electrolyte material and a preparation method thereof. The preparation method specifically comprises: (1) mixing a soluble aluminum salt and a precipitant in a molar ratio of 1:1.5-2 and dissolving them in water to obtain a mixed solution; then placing the mixed solution in a reaction kettle and heating it, filtering, washing and drying the product to obtain an AlOOH precursor; (2) mixing the AlOOH precursor obtained in step (1) with a lithium salt, a titanium salt and a phosphate salt according to a molar ratio of Li, Al, Ti and P of (1+x):x:(2-x):3, wherein x=0.3-0.5, adding ethanol medium and ball milling, and then pre-sintering and secondary molding sintering in a dry air atmosphere to obtain a lithium aluminum titanium phosphate solid electrolyte material.

[0005] However, the current LATP materials still have problems such as low grain boundary conductivity, high electrolyte brittleness, and large interface resistance when in contact with the positive and negative electrode materials of the battery.

[0006] As a commonly used method to change the crystal structure of materials, doping plays an important role in the modification of solid electrolytes, such as the doping of silicon (Journal of Power Sources, 2009, 189: 371-377). However, its improvement effect is effective.

[0007] Therefore, how to effectively improve the lithium aluminum titanium phosphate solid electrolyte and at the same time evenly distribute the elements without segregation is a technical problem that needs to be solved urgently. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lithium aluminum titanium phosphate solid electrolyte and its preparation method and application. The present invention achieves a significant improvement in the ionic conductivity of the lithium aluminum titanium phosphate solid electrolyte through the synergistic combination of boron and other doping elements (niobium and / or zinc), and reduces the sintering temperature in the preparation process and reduces the production energy consumption.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a lithium titanium aluminum phosphate solid electrolyte, wherein the lithium titanium aluminum phosphate solid electrolyte is doped with a first doping element and a second doping element; wherein the first doping element includes boron, and the second doping element includes niobium and / or zinc.

[0011] In the lithium aluminum titanium phosphate solid electrolyte provided by the present invention, boron cooperates with other doping elements (niobium and / or zinc) to achieve a significant improvement in ionic conductivity, so that the solid electrolyte material has more excellent electrochemical properties.

[0012] In the present invention, if the first doping element is not contained and only the second doping element (niobium and / or zinc) is included, the effect of lowering the sintering temperature cannot be achieved; and if only the first doping element is contained without the second doping element, that is, pure boron doping, the problem of low ion conductivity cannot be solved; that is, in the present invention, the first doping element (boron) and the second doping element (niobium and / or zinc) must cooperate with each other and neither can be missing, so as to achieve the purpose of reducing energy consumption while significantly improving ion conductivity.

[0013] In a second aspect, the present invention provides a method for preparing the lithium aluminum titanium phosphate solid electrolyte as described in the first aspect, the preparation method comprising the following steps:

[0014] A phosphorus source, a titanium source, an aluminum source, a lithium source, a first doping source, a second doping source and a solvent are mixed and sintered to obtain the lithium aluminum titanium phosphate solid electrolyte;

[0015] Wherein, the first doping source includes a boron source, and the second doping source includes a niobium source and / or a zinc source.

[0016] In the preparation method provided by the present invention, the first doping source can be used as a doping source and also as a flux, and is coordinated with the second doping source to reduce the sintering temperature, thereby reducing production energy consumption. Moreover, through simple solid-phase sintering, a lithium aluminum titanium phosphate solid electrolyte with a stable structure, uniform distribution of doping elements, and excellent ionic conductivity can be obtained.

[0017] Preferably, based on the total mass of the phosphorus source, titanium source, aluminum source, lithium source and the second doping source as 100%, the amount of the first doping source added is 1-2%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc.

[0018] In the present invention, if the amount of the first doping source added is too small, the sintering temperature cannot be reduced; and if it is too large, a large amount of impurities will appear in the material, affecting the ionic conductivity of the material.

[0019] Preferably, the boron source comprises a boron-containing oxide.

[0020] Preferably, the boron-containing oxide includes any one of boron trioxide, lithium metaborate or lithium tetraborate, or a combination of at least two thereof.

[0021] Preferably, based on the total mass of the phosphorus source, titanium source, aluminum source and lithium source as 100%, the amount of the second doping source added is 1-5%, for example, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8% or 5%, etc.

[0022] In the present invention, if the amount of the second doping source added is too small, it is not conducive to a significant improvement in the ionic conductivity of the material; and if it is too large, a large amount of impurities will appear in the material, affecting the ionic conductivity of the material.

[0023] Furthermore, the amount of the first doping source added in the present invention cooperates with the amount of the second doping source added, which can better achieve the purpose of reducing energy consumption while greatly improving ionic conductivity.

[0024] Preferably, the mixing comprises:

[0025] The phosphorus source and the solvent are first mixed, and then the titanium source, the aluminum source, the lithium source, the first doping source and the second doping source are added and second mixed.

[0026] In another preferred technical solution, other raw materials except the lithium source may be mixed first to obtain a precursor material, and then the lithium source is added for mixing.

[0027] Preferably, the first mixing time is 1 to 4 hours, such as 1 hour, 2 hours, 3 hours or 4 hours.

[0028] Preferably, the second mixing time is 4 to 10 h, for example, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.

[0029] Preferably, the mixed material is dried and sieved.

[0030] Preferably, the drying temperature is 70-120°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.

[0031] Preferably, the sieve has a mesh size of 50 to 400 meshes, such as 50 meshes, 100 meshes, 200 meshes, 300 meshes or 400 meshes.

[0032] Preferably, the sintering includes performing a first sintering and a second sintering in sequence.

[0033] Preferably, the heating rate of the first sintering is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0034] Preferably, the first sintering temperature is 500-700°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C.

[0035] Preferably, the first sintering time is 3 to 6 hours, such as 3 hours, 4 hours, 5 hours or 6 hours.

[0036] Preferably, the heating rate of the second sintering is 1-3°C / min, such as 1°C / min, 2°C / min or 3°C / min.

[0037] In the present invention, if the heating rate of the second sintering is too high, exceeding 3° C. / min, it will affect the size of the primary grains.

[0038] Preferably, the temperature of the second sintering is 800-1000°C, for example, 800°C, 830°C, 850°C, 900°C, 930°C, 950°C, 980°C or 1000°C.

[0039] In the sintering process of the present invention, there is no need for an excessively high sintering temperature. In particular, in the secondary sintering process, if the sintering temperature is too high, greater than 1000° C., not only a pure phase cannot be obtained, but the ionic conductivity of the material will be affected.

[0040] Preferably, the second sintering time is 5 to 10 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.

[0041] Preferably, the sintered material is crushed, ground, demagnetized and dried in sequence.

[0042] As a preferred technical solution, the preparation method comprises the following steps:

[0043] The phosphorus source and the solvent are first mixed for 1 to 4 hours, and then the titanium source, the aluminum source, the lithium source, the first doping source and the second doping source are added and second mixed for 4 to 10 hours; the second mixed material is dried and sieved;

[0044] The material is heated to 500-700° C. at a heating rate of 1-5° C. / min for a first sintering for 3-6 hours, and then heated to 800-1000° C. at a heating rate of 1-3° C. / min for a second sintering for 5-10 hours, and the material after the second sintering is crushed, ground, demagnetized and dried in sequence to obtain the lithium aluminum titanium phosphate solid electrolyte;

[0045] Among them, the first doping source includes a boron source, and the amount of the first doping source added is 1-2% based on the total mass of the phosphorus source, titanium source, aluminum source, lithium source and the second doping source as 100%; the second doping source includes a niobium source and / or a zinc source; based on the total mass of the phosphorus source, titanium source, aluminum source and lithium source as 100%, the amount of the second doping source added is 1-5%.

[0046] It should be noted that the lithium source, phosphorus source, aluminum source, titanium source, niobium source and zinc source in the present invention are all selected by conventional technology, that is, they can be used for the preparation of solid electrolytes and are suitable for the selection of raw materials for the preparation method of the present invention, and the present invention is applicable to all of them.

[0047] At the same time, the processing processes such as crushing, grinding, demagnetization and drying in the present invention are all conventional technical means, and the present invention does not limit the specific preparation process. The present invention is applicable to any solution that can achieve the above functions and is known to those skilled in the art.

[0048] In a third aspect, the present invention further provides a lithium-ion solid-state battery, wherein the lithium-ion solid-state battery comprises the lithium aluminum titanium phosphate solid-state electrolyte as described in the first aspect.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) In the lithium aluminum titanium phosphate solid electrolyte provided by the present invention, boron cooperates with other doping elements (niobium and / or zinc) to achieve a significant improvement in ionic conductivity, so that the solid electrolyte material has more excellent electrochemical properties.

[0051] (2) In the preparation method provided by the present invention, the first doping source can be used as a doping source and can also be used as a co-solvent, and is coordinated with the second doping source to reduce the sintering temperature, thereby reducing production energy consumption. Moreover, through simple solid-phase sintering, a lithium aluminum titanium phosphate solid electrolyte with a stable structure, uniform distribution of doping elements, and excellent ionic conductivity can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the XRD diagram of the lithium aluminum titanium phosphate solid electrolyte provided in Example 1.

[0053] Figure 2 This is the AC impedance diagram of the lithium aluminum titanium phosphate solid electrolyte provided in Example 1. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] Example 1

[0056] This embodiment provides a lithium titanium aluminum phosphate solid electrolyte, in which boron and niobium are doped simultaneously.

[0057] The preparation method of the lithium aluminum titanium phosphate solid electrolyte is as follows:

[0058] (1) Prepare raw materials: lithium carbonate, aluminum oxide, titanium oxide and ammonium dihydrogen phosphate are weighed respectively according to a molar ratio of 0.65:0.2:1.6:3, and the total mass of the above four raw materials is W1; niobium oxide is weighed, and its mass is 4% of W1 (i.e., W1 is 100%); the total mass of the above five raw materials is W2, and lithium tetraborate is weighed, and its mass is 1% of W2 (i.e., W2 is 100%); the mass ratio of anhydrous ethanol to total solid raw materials is 5:1, and the ball-to-material ratio is 7:1 (grinding beads);

[0059] Put ammonium dihydrogen phosphate, zirconium balls and 80% of the solvent into a ball mill and stir for 2 hours. After the first stage of stirring, put the remaining raw materials and solvent into the ball mill and stir for 8 hours. Then, put the obtained slurry into a non-metallic container, and place the mixed slurry in a vacuum oven for drying at a drying temperature of 80°C. After the material is dried, take it out and sieve it through a 200-mesh vibrating screen to obtain the sieved material.

[0060] (2) The sieved material is placed in a notched sagger with a loading capacity of 1.5 kg, and sintered in a roller kiln. The heating rate 1 is 5°C / min, the insulation platform 1 range is 700°C, and the insulation time is 4h (first sintering process); the heating rate 2 is 1°C / min, the insulation platform 2 is 850°C, and the insulation time is 6h (secondary sintering), and the temperature is slowly lowered for 4h;

[0061] The sintered material is cooled to room temperature, and after mechanical crushing and airflow crushing, it is sieved through a 200-mesh vibrating screen. The sieved material is added with a solvent according to a solid content of 25% and stirred into a slurry. The stirred slurry is ground by a demagnetizing sand mill. The sand mill rotor speed is 1300rpm and the grinding time is 6h. The ground slurry is demagnetized by a liquid circulation demagnetization device for 6h. The demagnetized slurry is dried by a VC dryer, and the dried material is crushed into powder by airflow crushing to obtain the lithium titanium aluminum phosphate solid electrolyte.

[0062] Example 2

[0063] This embodiment provides a lithium titanium aluminum phosphate solid electrolyte, in which boron and niobium are doped simultaneously.

[0064] The preparation method of the lithium aluminum titanium phosphate solid electrolyte is as follows:

[0065] (1) Prepare raw materials: lithium carbonate, aluminum oxide, titanium oxide and ammonium dihydrogen phosphate are weighed respectively according to a molar ratio of 0.65:0.2:1.6:3, and the total mass of the above four raw materials is W1; niobium oxide is weighed, and its mass is 1% of W1 (i.e., W1 is 100%); the total mass of the above five raw materials is W2, and boron trioxide is weighed, and its mass is 2% of W2 (i.e., W2 is 100%); the mass ratio of anhydrous ethanol to total solid raw materials is 5:1, and the ball-to-material ratio is 7:1 (grinding beads);

[0066] Put ammonium dihydrogen phosphate, zirconium balls and 80% of the solvent into a ball mill and stir for 4 hours. After the first stage of stirring, put the remaining raw materials and solvent into the ball mill and stir for 10 hours. Then, put the obtained slurry into a non-metallic container, and place the mixed slurry in a vacuum oven for drying at a drying temperature of 80°C. After the material is dried, take it out and sieve it through a 300-mesh vibrating screen to obtain the sieved material.

[0067] (2) The sieved material is placed in a notched sagger with a loading capacity of 1.5 kg, and sintered in a roller kiln. The heating rate 1 is 5°C / min, the insulation platform 1 range is 700°C, and the insulation time is 4 hours (first sintering process); the heating rate 2 is 3°C / min, the insulation platform 2 is 1000°C, and the insulation time is 5 hours (secondary sintering), and the temperature is slowly lowered for 4 hours;

[0068] The sintered material is cooled to room temperature, and after mechanical crushing and air flow crushing, it is sieved through a 200-mesh vibrating screen. The sieved material is added with a solvent according to a solid content of 25% and stirred into a slurry. The stirred slurry is ground by a demagnetizing sand mill. The sand mill rotor speed is 1500rpm and the grinding time is 8h. The ground slurry is demagnetized by a liquid circulation demagnetization device for 8h. The demagnetized slurry is dried by a VC dryer, and the dried material is crushed into powder by air flow crushing to obtain the lithium titanium aluminum phosphate solid electrolyte.

[0069] Example 3

[0070] The difference between this embodiment and embodiment 1 is that in this embodiment, niobium oxide is replaced by zinc oxide.

[0071] The rest of the preparation methods and parameters were the same as those in Example 1.

[0072] Example 4

[0073] The difference between this embodiment and embodiment 1 is that in this embodiment, niobium oxide is replaced by zinc oxide, and the amount of lithium tetraborate added is 2%.

[0074] The rest of the preparation methods and parameters were the same as those in Example 1.

[0075] Example 5

[0076] The difference between this embodiment and embodiment 1 is that the amount of lithium tetraborate added in this embodiment is 3%.

[0077] The rest of the preparation methods and parameters were the same as those in Example 1.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that the amount of lithium tetraborate added in this embodiment is 0.5%.

[0080] The rest of the preparation methods and parameters were the same as those in Example 1.

[0081] Example 7

[0082] The difference between this embodiment and embodiment 1 is that the amount of niobium oxide added in this embodiment is 6%.

[0083] The rest of the preparation methods and parameters were the same as those in Example 1.

[0084] Example 8

[0085] The difference between this embodiment and embodiment 1 is that the heating rate 2 in step (2) of this embodiment is 5° C. / min.

[0086] The rest of the preparation methods and parameters were the same as those in Example 1.

[0087] Example 9

[0088] The difference between this embodiment and embodiment 1 is that the temperature of the secondary sintering in step (2) of this embodiment is 1100°C.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Comparative Example 1

[0091] The difference between this comparative example and Example 1 is that the solid electrolyte provided in this comparative example is doped with only niobium but not boron, and lithium tetraborate is not added in the preparation method.

[0092] The rest of the preparation methods and parameters were the same as those in Example 1.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that the solid electrolyte provided in this comparative example is doped with only boron but not niobium, and niobium oxide is not added in the preparation method.

[0095] The rest of the preparation methods and parameters were the same as those in Example 1.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 2 is that the solid electrolyte provided in this comparative example is doped with only boron but not niobium, and niobium oxide is not added in the preparation method.

[0098] The rest of the preparation methods and parameters were the same as those in Example 1.

[0099] Comparative Example 4

[0100] The difference between this comparative example and Example 3 is that the solid electrolyte provided in this comparative example is doped with only niobium but not boron, and lithium tetraborate is not added in the preparation method.

[0101] The rest of the preparation methods and parameters were the same as those in Example 3.

[0102] Comparative Example 5

[0103] The difference between this comparative example and Example 1 is that no doping is performed in the solid electrolyte provided in this comparative example.

[0104] In the preparation method, neither niobium oxide nor lithium tetraborate is added.

[0105] Figure 1 The XRD pattern of the lithium aluminum titanium phosphate solid electrolyte provided in Example 1 is shown. Figure 1 It can be seen that the XRD diffraction pattern prepared under the experimental conditions is consistent with the standard spectrum of LATP, and the material phase formation accuracy is good.

[0106] Figure 2 The AC impedance diagram of the lithium aluminum titanium phosphate solid electrolyte provided in Example 1 is shown. Figure 2 It can be seen that the solid electrolyte material provided in this embodiment has a small impedance and a high ion conductivity.

[0107] The solid electrolyte materials provided in Examples 1-9 and Comparative Examples 1-5 were tested for ion conductivity, and the specific test conditions were: the material was prepared as a disc with a thickness of 0.5 mm to 1 mm, a smooth surface, a density of >95%, a test temperature of 25±2°C, and a humidity of <50%.

[0108] Table 1

[0109] Ionic conductivity (S / cm) Example 1 <![CDATA[6.20×10 -4 ]]> Example 2 <![CDATA[5.85×10 -4 ]]> Example 3 <![CDATA[5.98×10 -4 ]]> Example 4 <![CDATA[5.58×10 -4 ]]> Example 5 <![CDATA[3.52×10 -4 ]]> Example 6 <![CDATA[2.87×10 -4 ]]> Example 7 <![CDATA[2.56×10 -4 ]]> Example 8 <![CDATA[4.35×10 -4 ]]> Example 9 <![CDATA[3.26×10 -4 ]]> Comparative Example 1 <![CDATA[2.10×10 -4 ]]> Comparative Example 2 <![CDATA[1.86×10 -4 ]]> Comparative Example 3 <![CDATA[1.20×10 -4 ]]> Comparative Example 4 <![CDATA[1.56×10 -4 <!-- 6 -->]]> Comparative Example 5 <![CDATA[7.5×10 -5 ]]>

[0110] From the data results of Example 1 and Examples 5-7, it can be seen that if the amount of boron source (first doping source) added is too little, it is not conducive to lowering the sintering temperature, and if it is too much, it will affect the physical purity and ionic conductivity of the material; and if the amount of the second doping source added is too much, it will lead to a decrease in ionic conductivity; that is, the amount of the first doping source and the second doping source added cooperates to achieve the purpose of both lowering the sintering temperature and improving the ionic conductivity.

[0111] From the data results of Example 1 and Example 8, it can be seen that if the heating rate in the second sintering process is too high, the ionic conductivity of the material will decrease. The reason is that the heating rate is too fast, resulting in uneven grain distribution and lithium ions cannot be well transferred and transported between grains.

[0112] It can be seen from the data results of Example 1 and Example 9 that the sintering temperature in the second sintering process is too high, which is not conducive to obtaining a high ionic conductivity material.

[0113] From the data results of Examples 1-4 and Comparative Examples 1-5, it can be seen that the present invention achieves the purpose of lowering the sintering temperature and improving the ionic conductivity by the synergistic combination of boron and the second doping element (niobium and / or zinc).

[0114] In summary, in the lithium aluminum titanium phosphate solid electrolyte provided by the present invention, boron cooperates with other doping elements (niobium and / or zinc) to achieve a significant improvement in ionic conductivity, so that the solid electrolyte material has more excellent electrochemical properties; at the same time, the boron source also plays the role of a flux in the preparation process, reducing the sintering temperature, thereby reducing production energy consumption.

[0115] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A lithium aluminum titanium phosphate solid electrolyte, characterized in that: The lithium aluminum titanium phosphate solid electrolyte is doped with a first doping element and a second doping element; wherein the first doping element includes boron, and the second doping element includes niobium and / or zinc.

2. A method for preparing the lithium aluminum titanium phosphate solid electrolyte as claimed in claim 1, characterized in that: The preparation method comprises the following steps: A phosphorus source, a titanium source, an aluminum source, a lithium source, a first doping source, a second doping source and a solvent are mixed and sintered to obtain the lithium aluminum titanium phosphate solid electrolyte; Wherein, the first doping source includes a boron source, and the second doping source includes a niobium source and / or a zinc source.

3. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 2, characterized in that: Based on the total mass of the phosphorus source, the titanium source, the aluminum source, the lithium source and the second doping source being 100%, the added amount of the first doping source is 1-2%.

4. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to claim 2 or 3, characterized in that: The boron source includes a boron-containing oxide; Preferably, the boron-containing oxide includes any one of boron trioxide, lithium metaborate or lithium tetraborate, or a combination of at least two thereof.

5. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to any one of claims 2 to 4, characterized in that: Based on the total mass of the phosphorus source, the titanium source, the aluminum source and the lithium source being 100%, the added amount of the second doping source is 1-5%.

6. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to any one of claims 2 to 5, characterized in that: The mixing includes: The phosphorus source and the solvent are first mixed, and then the titanium source, the aluminum source, the lithium source, the first doping source and the second doping source are added to perform a second mixing; Preferably, the first mixing time is 1 to 4 hours; Preferably, the second mixing time is 4 to 10 hours.

7. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to any one of claims 2 to 6, characterized in that: Drying and sieving the mixed material; Preferably, the drying temperature is 70-120°C; Preferably, the mesh size of the sieving is 50-400 meshes.

8. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to any one of claims 2 to 7, characterized in that: The sintering includes sequentially performing a first sintering and a second sintering; Preferably, the heating rate of the first sintering is 1-5°C / min; Preferably, the first sintering temperature is 500-700°C; Preferably, the first sintering time is 3 to 6 hours; Preferably, the heating rate of the second sintering is 1-3°C / min; Preferably, the temperature of the second sintering is 800-1000°C; Preferably, the second sintering time is 5 to 10 hours; Preferably, the sintered material is crushed, ground, demagnetized and dried in sequence.

9. The method for preparing the lithium aluminum titanium phosphate solid electrolyte according to any one of claims 2 to 7, characterized in that: The preparation method comprises the following steps: The phosphorus source and the solvent are first mixed for 1 to 4 hours, and then the titanium source, the aluminum source, the lithium source, the first doping source and the second doping source are added and second mixed for 4 to 10 hours; the second mixed material is dried and sieved; The material is heated to 500-700° C. at a heating rate of 1-5° C. / min for a first sintering for 3-6 hours, and then heated to 800-1000° C. at a heating rate of 1-3° C. / min for a second sintering for 5-10 hours, and the material after the second sintering is crushed, ground, demagnetized and dried in sequence to obtain the lithium aluminum titanium phosphate solid electrolyte; Among them, the first doping source includes a boron source, and the amount of the first doping source added is 1-2% based on the total mass of the phosphorus source, titanium source, aluminum source, lithium source and the second doping source as 100%; the second doping source includes a niobium source and / or a zinc source; based on the total mass of the phosphorus source, titanium source, aluminum source and lithium source as 100%, the amount of the second doping source added is 1-5%.

10. A lithium-ion solid-state battery, characterized in that: The lithium-ion solid-state battery includes the lithium titanium aluminum phosphate solid-state electrolyte as claimed in claim 1.

Citation Information

Patent Citations

  • LATP-applied lithium ion battery positive electrode material and preparation method

    CN111180703A

  • Lithium titanium aluminum phosphate solid electrolyte material and preparation method thereof

    CN111233458A